‘Safety is about partnership’: Safety through the lens of patients and caregivers - Kerry Kuluski; Maaike Asselbergs; Ross Baker; Katharina (Kathy) Kovacs Burns; Frances Bruno; Marianne Saragosa; Anne MacLaurin; Virginia Flintoft; Lianne Jeffs (Health Expectations)
Abstract Introduction Creating safer care is a high priority across healthcare systems. Despite this, most systems tend to focus on mitigating past harm, not creating proactive solutions. Managers and staff identify safety threats often with little input from patients and their caregivers during their health encounters. Methods This is a qualitative descriptive study utilizing focus groups and one‐to‐one interviews with patients and caregivers who were currently using (or had previously used) services in health systems across Canada. Data were analysed via inductive thematic analysis to understand existing and desired strategies to promote safer and better quality care from the perspectives of patients and caregivers. Findings In our analysis, we identified three key themes (safety strategies) from patients' and caregivers' perspectives and experiences: Using Tools and Approaches for Engaging Patients and Caregivers in their Care; Having Accountability Processes and Mechanisms for Safe Care; and Enabling Patients and Caregivers Access to Information. Conclusions Safety is more than the absence of harm. Our findings outline a number of suggestions from patients and caregivers on how to make care safer, ranging from being valued on teams, participating as members of quality improvement tables, having access to health information, having access to an advocate to help make sense of information and having processes in place for disclosure and closure. Future work can further refine, implement and evaluate these strategies in practice. Patient or Public Contributions An advisory group guided the research and was co‐chaired by a patient partner. Members of the advisory group spanned patient and caregiver organizations and health sectors across Canada and included three patient partners and leaders who work closely with patients and caregivers in their day‐to‐day work. In the research itself, we engaged 28 patients and caregivers from across Canada to learn about their safety experiences and learn what safer care looks like from their perspectives.